Historically Informed Looks at Gender – Not Only for Historians (KULT_online, 2011)
With her introductory book Geschlechtergeschichte (Gender History), Claudia Opitz-Belakhal presents an historical overview of 'gender.' Part of the historical introduction series by Campus, this monograph defines the most important key concepts, such as 'gender' and 'queer,' in relation to several other issues, such as the women's movement, historiography, and postcolonial studies. Spanning many decades, this short but very informative introductory work offers not only an historical research perspective, but also an interdisciplinary and intercultural one.